GENETIC DISORDERS OF RED CELL GLYCOLYSIS : A REVIEW FROM THE MOLECULAR TO CLINICAL AND THERAPEUTIC APROACHES - SOPHIA DELICOU; THEONI KANELLOPOULOU; CHRYSSANTHI KONTAXI; ARGIRI VLACHOPOULOU; ZOI PALANTZA; KONSTANTINOS MARAGKOS (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
The erythrocyte, devoid of nucleus, mitochondria,ribosomes and other organelles, has no capacity for cell replication, protein synthesis, or oxidative phosphorylation.